Rancang Bangun Aplikasi Food Waste Management pada Usaha Food and Beverages - Heni Rachmawati Santoso; Syefrida Yulina (Politeknik Caltex Riau, 2023)
Food waste management should be an essential concern in the food and beverages (F&B) industries. FAO notes that the F&B business is one of the causes of food waste, both from the production level to consumer consumption. This study aims to help F&B businesses have a food waste management application, as well as help recommend menus that have a lower probability of food waste appearing. The study uses queuing techniques in handling material stocks and conducting food waste audits by documenting the groupings of the waste produced. The results of the two previous functions become input for the menu recommendation process with minimal waste based on the Contextual Model approach and Multi-Criteria Decision Making (MCDM). The results show that the queuing mechanism in handling material stocks has succeeded in reducing COGS by 24.8%. The waste audit succeeded in calculating the percentage of food loss and food waste that appeared, and the menu recommendations succeeded in providing the best alternative that minimized the appearance of waste